Historical thinking and representation in Caryl Phillips’s Higher ground and J. M. Coetzee’s Dusklands - Stefanova Radoulska, Svetlana (Epos : Revista de filología, 2012)
This study is an attempt to cross the boundaries between academic disciplines and provide a new perspective for the interpretation of the past in J. M. Coetzee’s Dusklands (1974) and Caryl Phillips’s Higher Ground (1989). The analysis of the narrative strategies the two authors share to expose patterns of socially and ideologically constructed representation of the historical «other» draws on some of the main ideas and concepts developed by Frank Ankersmit, one of the leading figures in contemporary historiography. Reflecting on the relation between interpretation, truth, and the meaning given to past reality, the present article reads the fragments of representations of the past as «narrative substances» and examines the choice and arrangement of these fragments in the two novels. The way individual stories of suffering are interconnected to stand as a «whole» helps our understanding of the discursive practices in the production of knowledge about the past and reveals their power and limitations. El presente estudio constituye un intento de cruzar los límites entre las disciplinas académicas y aportar una perspectiva novedosa a la interpretación del pasado en Dusklands (1974) de J. M. Coetzee y Higher Ground (1989) de Caryl Phillips. El análisis de las estrategias narrativas que comparten ambos autores para exponer patrones de representación construidos sociológica e ideológicamente del «otro» histórico se basa en algunas de las ideas y conceptos desarrollados por Frank Ankersmit, una de las figuras más relevantes dentro de la historiografía contemporánea. Reflexionando acerca de la relación entre interpretación, verdad, y el significado que se otorga a la realidad pasada, este artículo lee los fragmentos de las representaciones del pasado como «sustancias narrativas», examinando la elección y disposición de dichos fragmentos en las dos novelas analizadas. La manera en la que las se interconectan las historias individuales de sufrimiento para constituir un «todo» coadyuva a nuestro entendimiento de las prácticas discursivas en la producción del conocimiento acerca del pasado y revela su poder y sus limitaciones.